Delivery of Potential Drugs to The Colon: Challenges and Strategies - Raditya Iswandana; Kurnia Sari Setio Putri; Sekar Arum Larasati; Maxius Gunawan; Fathia Amalia Putri (Indonesian Journal of Pharmacy, 2022)
Colon-targeted drug delivery systems have been exploited to treat local diseases in the colon, systemic delivery of protein and peptide, and chronotherapeutic drugs. The upper gastrointestinal tract restricts the effective delivery of these drugs. Therefore, several strategies are needed for targeted drugs directly to the colon, such as pH-sensitive polymers, enzyme-sensitive polymers, bacterially degradable polysaccharides, time-dependent polymers, and particulate systems. However, variable physiological conditions of the gastrointestinal tract in individuals cause combinations of these strategies are needed to ensure colonic delivery of the drug. This review presents and discusses several potential drugs and their approaches used to design and develop colon-targeted drug delivery systems for medications with particular characteristics.